Improving Gross Motor Ability Through Circuit Games For Children Group B - Adrikni, Khilati (Prosiding University Research Colloquium, 2021)
This study aims to determine the improvement of gross motor skills through circuit games for children aged group B in RA P2A Salaman. This type of research is classroom action research that uses 2 cycles with stages including planning, implementation, observation and reflection stages. The research subjects were students of group B in RA P2A Salaman, totaling 16 children consisting of 9 girls and 7 boys. The data collection method uses non-test in the form of observation. Based on the results of the research and discussion, it can be concluded that the gross motor skills of child B in RA P2A Salaman can be improved through circuit games. The increase that occurs can be seen from the research stage, namely observations made during pre-action, implementation of actions in cycle I and cycle II. This is indicated by the results achieved by the subject from the initial conditions or before the gross motor ability action was carried out in the low category. Group B in RA P2A Salaman experienced an increase in gross motor skills from pre-cycle by 4.93%, increased in cycle I to 9.8% and increased to 12.8% in cycle II. From these results it can be seen that the gross motor skills of children have reached the success criteria expected by researchers.